KINERJA STRUKTUR GEDUNG TINGGI MATARAM CITY MENGGUNAKAN STUDY PEMODELAN BASEMENT - R. Lintang Gumilang B; Sunarmasto Sunarmasto; Achmad Basuki (Program Studi Teknik Sipil FT UNS, 2014)
Indonesia is a country prone to earthquakes. The high potential earthquake caused Indonesia's geographical position between the world's threetectonic plates, the Eurasian plate, Australia, and the Philippines. The high earthquake potential demand for reliable and secure building becomesa necessity. Availability of land makes more narrow tall buildings into alternative development today. There are two approaches used to account forlateral loads (earthquakes) are working on a structure, the equivalent static analysis and dynamic analysis This study aims to determine the safetyof the building after a redesign that seen in the basement of the displacement, drift and base shear. The results of this study analyzed theperformance of the structure and the serviceability limit ultimate performance limit structure. The method used is the dynamic response spectrumanalysis using ETABS program V 13.1.3. Raft Fondation can use for high rise building. Value of displacement in the X direction is 0.1046 mand the Y direction is 0.1090 m. The maximum total drift in the direction of X is 0.00202 m and the Y direction is 0.00211 m, so that thebuilding is safe for ultimate performance limit (0.02 h) and serviceability limit performance (0.03 / R) xh. Displacement at Mataram Citybuilding does not exceed the maximum displacement and safe against earthquake plan.